2009
DOI: 10.1016/j.athoracsur.2009.03.085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Failing Fontans for Heart Transplantation: Predictors of Death

Abstract: Background Late complications of the Fontan operation represent a significant management challenge. In general, failing Fontan patients have two modes of presentation: those with impaired ventricular function (IVF group) and those with preserved ventricular function but with failing Fontan physiology (protein-losing enteropathy-PLE, and plastic bronchitis-PB) (PVF group). In this study we evaluated whether failing Fontan patients referred for heart transplantation had a different outcome based on the mode of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(110 citation statements)
references
References 25 publications
1
106
0
3
Order By: Relevance
“…In our adult patients undergoing transplant for FFP, we identified preserved ventricular function as an independent predictor of mortality (24). Griffiths et al verified this in a younger cohort when they reported 1-year survival after OHT in impaired ventricular function patients at 88.9%, compared to 56.2% in those with preserved ventricular function, 80% of whom had PLE or PB (25).…”
Section: The Fontan Patientmentioning
confidence: 65%
See 1 more Smart Citation
“…In our adult patients undergoing transplant for FFP, we identified preserved ventricular function as an independent predictor of mortality (24). Griffiths et al verified this in a younger cohort when they reported 1-year survival after OHT in impaired ventricular function patients at 88.9%, compared to 56.2% in those with preserved ventricular function, 80% of whom had PLE or PB (25).…”
Section: The Fontan Patientmentioning
confidence: 65%
“…PLE and PB present exclusively in patients with preserved ventricular function following Fontan completion (25). PLE is characterized by abnormal serum protein loss into the gut lumen.…”
Section: Ple and Pbmentioning
confidence: 99%
“…The relative infrequency of PLE, combined with our rudimentary knowledge of the interplay between the cardiovascular and lymphatic systems, has hindered understanding of the pathophysiologic processes underlying this disease, as well as the development of effective therapy. Transplantation is often the only reasonable option [5,6]. Historically, survival after diagnosis has been 50% at 5 years [4,7].…”
Section: Commentmentioning
confidence: 99%
“…PLE prior to transplantation is associated with a poor long term outcome. (158,159) With improving early survival from staged Fontan surgery, there will be an inevitable increase in adults with failing Fontan circulations in whom transplantation will be considered. The prospect of a mechanical Fontan support device has been raised and a number of designs have undergone mathematical modeling (160,161) and animal studies.…”
Section: Role Of Transplantationmentioning
confidence: 99%